Strategic analysis and plan of BF Industries, Inc. - Fernandez, Beatriz M. (School of Management, University of the Philippines Mindanao, 2007)
In the last two decades, the activated carbon industry has experienced an increase in the number of competitors. In the Philippines, competition for the supply of raw material is the main concern rather than competition for the market. Other producers of coconut shell charcoal based activated carbon are based in Indonesia, Thailand, Malaysia, Sri Lanka, India, Vietnam, and China. The global activated carbon demand will increase 5% annually until 2010. Mature markets such as North America, Western Europe and Japan will remain to be dominant while China will gain market share. Smaller market like Latin America, Eastern Europe, Africa, and the Middle East will also grow at above average rates. It is proposed in this paper that BF Industries, Inc. pursue a concentric diversification strategy for the company. With the same technology, markets, and products, the company will introduce a business related to its business. This strategy will help gain benefits from its strengths and opportunities and decrease the level of weaknesses and threats.